EFFECT OF TRANSFORMATIONAL AND TRANSACTIONAL LEADERSHIP STYLE ON PUBLIC HEALTH CENTRE PERFORMANCE - Agus Purwanto; Innocentius Bernarto; Masduki Asbari; Laksmi Mayesti Wijayanti; Choi Chi Hyun (Kusuma Negara Business School, 2020)
This study aims to analyze the effect of transformational and transactional leadership styles on the performance of Health Center or Puskesmas in Pati, Central Java. The research respondents were employees and staff at the Puskesmas 120 people and the method of data collection was by giving an electronic questionnaire to respondents who were distributed randomly in December 2019. This research analysis tool uses SEM (Structural Equation Model) LISREL program version 8.70. Based on the data analysis shows that the transformational leadership style has a positive and strongly significant effect on the performance of puskesmas employees and the transactional leadership style also has a strongly significant and positive effect on puskesmas employee performance.The research suggestion is the leadership style of the Puskesmas head should use transactional and transfromational style such as instruction, consultation, participation and delegation with the performance of Puskesmas staff such as attendance, cooperation, quality of work, attitudes, and knowledge about work to solve everyday problems. Puskesmas leaders must adopt a more flexible leadership style in accordance with the existing situation for better performance of Puskesmas staff.